A pandemia invisível: o sofrimento em tempos pandêmicos e o aconselhamento pastoral como caminho de ressignificação da vida - Ferreira, Fabiana de Oliveira (2022)
Suffering permeates the dimensions of human life in various aspects, as well as different times and moments, and can be broad in its experience. The present research aimed, in pandemic times where efforts are normally aimed at helping life itself and automatically in the direct fight against the virus/disease, situations of suffering, which can reverberate in an illness, especially mental, and which can be forgotten, causing an invisible pandemic. In this path, the hypothesis of this research is that pastoral counseling can be is a path to comprehensive interdisciplinary care, in the relationship between health and religion, for the resignification of life in pandemic times. Considering that we are still during the Covid-19 pandemic, this bibliographic research was based on a dialogue with the events, in the field of health and religion, between the Spanish Flu and Covid-19 in Brazil, especially in the concerning situations of suffering. As the main results, we investigated the correlation between the spaces of suffering and the way it presents itself in both pandemics, as well as its relationship with faith and health. In addition, we address the benefits that spirituality/religion can provide to human beings in terms of integral health and its therapeutic actions. And finally, we point out pastoral counseling as a path of care within an interdisciplinary context, to minimize the suffering of what we name in this dissertation as an invisible pandemic.(AU)